(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of the competence and independence of the audit committee on the quality of audits of financial statements in banking companies listed on the Indonesia Stock Exchange. According to the formulation of the problem stated in the previous chapter, it can be concluded that the competence of the audit committee has an effect on audit quality in banking companies listed on the Indonesia Stock Exchange. This research was conducted on banking registered on the Indonesia Stock Exchange. Banking companies listed on the Indonesia Stock Exchange for the period 2013-2017 that have been audited for five years, namely 23 banks. The independence of the audit committee influences the audit quality of banking companies listed on the Indonesia Stock Exchange. The competence and independence of audit committee members affect audit quality in banking companies listed on the Indonesia Stock Exchange.